“We Just Did Not Get on”. Young Adults’ Experiences of Unsuccessful Psychodynamic Psychotherapy – A Lack of Meta-Communication and Mentalization? - von Below, Camilla (Frontiers in Psychology, 2020)
In order to avoid suboptimal psychotherapy, research needs to highlight and analyze obstacles in such treatments. This clinically oriented article brings together empirical material of unsuccessful psychotherapy with young adults, empirical material on the therapists’ views of the same therapies, and theoretical perspectives on mentalization, therapeutic alliance and young adulthood. Through a secondary qualitative analysis, it presents a tentative process model of how suboptimal psychotherapy with young adults develops, how it could be handled clinically, and possibly prevented. In three studies, experiences of young adult patients (aged 18-25; n=27) in psychoanalytic therapy at an outpatient clinic, who did not improve from therapy (defined as no reliable and clinically significant symptom reduction) and/or were dissatisfied, and their therapists, were analyzed. Patients described experiences of not being understood and not understanding therapy, whereas therapists described patient non-commitment. These results were compared from the developmental perspective of mentalization in young adulthood. The primary Grounded Theory analyses and secondary analysis resulted in a tentative process model of the development of suboptimal psychotherapy with young adults. Suboptimal therapy is described as a vicious circle of therapist underestimation of patient problems, therapeutic interventions on an inadequate level, diverging agendas between therapist and patient in terms of therapeutic alliance, resulting in pseudo-mentalizing and no development towards agency. A benign circle of successful therapy is characterized by correct estimation of patient problems, meta-communication and the repair of alliance ruptures. One clinical implication is that therapists of young adult patients need to establish verbal and nonverbal meta-communication on therapy progress and therapeutic alliance. The importance of the patients’ present mentalization capacity and adjusted interventions is demonstrated in an example. Research in the field should be process-oriented and investigate the effect of meta-communication and interventions targeted to foster therapeutic alliance based on this theoretical model, particularly for young adults.